2022
DOI: 10.1038/s41598-022-15662-0
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and semidiurnal internal waves on the southern slope of the Yermak Plateau

Abstract: The Yermak Plateau (YP) is located across the Arctic–Atlantic gateway in the northwest of the Svalbard archipelago. In this region, internal waves are believed to cause intense turbulent mixing and hence influence the heat budget in the Arctic Ocean. Based on year-long observations from three moorings, the characteristics and energetics of diurnal and semidiurnal internal waves on the southern slope of the YP are investigated in this study. Diurnal internal waves induce large isothermal displacements exceeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…“Baroclinic” velocities and shear spectra (Figures 9, 13, and 14; Figures S1 and S2 in Supporting Information ) show a dominant peak around the semi‐diurnal period while velocity spectra show a dominant peak at the diurnal frequency (Figure 3). This is consistent with recent mooring observations on the southwestern slope of the Yermak Plateau (6E, 79°40’) (Wang et al., 2022). Their observations suggest that a strong diurnal barotropic tide impinging on the slope can generate internal waves at higher harmonics, in particular, semi‐diurnal internal waves.…”
Section: Internal Waves and Near‐inertial Wavessupporting
confidence: 93%
See 2 more Smart Citations
“…“Baroclinic” velocities and shear spectra (Figures 9, 13, and 14; Figures S1 and S2 in Supporting Information ) show a dominant peak around the semi‐diurnal period while velocity spectra show a dominant peak at the diurnal frequency (Figure 3). This is consistent with recent mooring observations on the southwestern slope of the Yermak Plateau (6E, 79°40’) (Wang et al., 2022). Their observations suggest that a strong diurnal barotropic tide impinging on the slope can generate internal waves at higher harmonics, in particular, semi‐diurnal internal waves.…”
Section: Internal Waves and Near‐inertial Wavessupporting
confidence: 93%
“…Possibly, interactions of freely propagating internal waves at period 2K1 (11.97 hr) generated and propagated from both eastern and western slopes of the rather narrow plateau could lead to stationary waves as observed here. Further moorings in the Yermak Plateau complementing observations by Wang et al (2022) on the southwestern slope and the present ones on the eastern slope are needed to test this hypothesis.…”
Section: Possible Physical Interpretation Of the Shear Signalsmentioning
confidence: 81%
See 1 more Smart Citation
“…"Baroclinic" velocities and shear spectra (Figures 9,13,and 14;Figures S1 and S2 in Supporting Information S1) show a dominant peak around the semi-diurnal period while velocity spectra show a dominant peak at the diurnal frequency (Figure 3). This is consistent with recent mooring observations on the southwestern slope of the Yermak Plateau (6E, 79°40') (Wang et al, 2022). Their observations suggest that a strong diurnal barotropic tide impinging on the slope can generate internal waves at higher harmonics, in particular, semi-diurnal internal waves.…”
Section: Possible Physical Interpretation Of the Shear Signalssupporting
confidence: 92%
“…It was shown that the strength of the diurnal barotropic tide and the steepness of the slope are controlling factors in producing internal waves at higher harmonics and solitary waves. New mooring observations on the Southwestern slope of the Yermak Plateau documented strong barotropic diurnal tides triggering internal waves at higher harmonics, in particular at the semi-diurnal period (Wang et al, 2022). It is to be noted that the second harmonic (period 11.97 hr) of the diurnal tide is not subinertial over the Yermak Plateau and could freely propagate.…”
Section: Introductionmentioning
confidence: 94%